4
$\begingroup$

I was playing with some combinatorial sums and made an observation that I didn't know how to prove: $$\forall n\in\mathbb N,\hspace{10px}\sum_{k=1}^n\frac{B_k\ S_1(n-1,\,k-1)}k=-\sum_{k=1}^n\frac{S_1(n,\,k)}{(k+1)\ n},$$ where $B_k$ are Bernoulli numbers and $S_1(n,\,k)$ are signed Stirling numbers of the first kind.

Could you please suggest any ideas how to prove it?

$\endgroup$
6
$\begingroup$

Suppose we seek to show that $$\sum_{k=1}^n \frac{B_k}{k} (-1)^{n-k} {n-1\brack k-1} = -\frac{1}{n} \sum_{k=1}^n \frac{1}{k+1} (-1)^{n-k} {n\brack k}.$$

Recall the classic generating function of the Stirling numbers of the first kind which yields $${n\brack k} = n! [z^n][u^k] \exp\left(u\log\frac{1}{1-z}\right).$$ and also $${n\brack k} = n! [z^n] \frac{1}{k!}\left(\log\frac{1}{1-z}\right)^k$$ which controls the range so that for $n\lt k$ we get zero, and hence we may let $k$ go to infinity in the two sums.

We get for the LHS $$(n-1)! [z^{n-1}] \sum_{k=1}^\infty \frac{B_k}{k} (-1)^{n-k} \frac{1}{(k-1)!} \left(\log\frac{1}{1-z}\right)^{k-1} \\ = (n-1)! (-1)^n [z^{n-1}] \sum_{k=1}^\infty \frac{B_k}{k!} (-1)^{k} \left(\log\frac{1}{1-z}\right)^{k-1} \\ = (n-1)! (-1)^n [z^{n-1}] \left(\log\frac{1}{1-z}\right)^{-1} \sum_{k=1}^\infty \frac{B_k}{k!} (-1)^{k} \left(\log\frac{1}{1-z}\right)^{k}.$$

We recognize the exponential generating function of the Bernoulli numbers which is $$\frac{w}{e^w-1}.$$ The initial term is missing from the sum so we use $$-1+\frac{w}{e^w-1}.$$ and obtain $$(n-1)! (-1)^n [z^{n-1}] \left(\log\frac{1}{1-z}\right)^{-1} \left(-1 - \log\frac{1}{1-z} \frac{1}{\exp\left(-\log\frac{1}{1-z}\right)-1}\right) \\ = (n-1)! (-1)^n [z^{n-1}] \left(\log\frac{1}{1-z}\right)^{-1} \left(-1 - \log\frac{1}{1-z} \frac{1}{(1-z)-1}\right) \\ = (n-1)! (-1)^n [z^{n-1}] \left(-\left(\log\frac{1}{1-z}\right)^{-1} + \frac{1}{z}\right).$$

Continuing with the RHS we obtain $$-\frac{1}{n} n! [z^n] \sum_{k=1}^\infty \frac{1}{k+1} (-1)^{n-k} \frac{1}{k!}\left(\log\frac{1}{1-z}\right)^k \\ = -(n-1)! (-1)^n [z^n] \sum_{k=1}^\infty \frac{1}{k+1} (-1)^{k} \frac{1}{k!}\left(\log\frac{1}{1-z}\right)^k \\ = -(n-1)! (-1)^n [z^n] \sum_{k=1}^\infty (-1)^{k} \frac{1}{(k+1)!}\left(\log\frac{1}{1-z}\right)^k \\ = (n-1)! (-1)^n [z^n] \left(\log\frac{1}{1-z}\right)^{-1} \sum_{k=1}^\infty (-1)^{k+1} \frac{1}{(k+1)!}\left(\log\frac{1}{1-z}\right)^{k+1}.$$

This time we recognize $$-1-w+\exp(w)$$ to get $$(n-1)! (-1)^n [z^n] \left(\log\frac{1}{1-z}\right)^{-1} \left(-1+\log\frac{1}{1-z} + \exp\left(-\log\frac{1}{1-z}\right)\right) \\ = (n-1)! (-1)^n [z^n] \left(\log\frac{1}{1-z}\right)^{-1} \left(-1+\log\frac{1}{1-z} + 1-z\right) \\ = (n-1)! (-1)^n [z^n] \left(1 - z\left(\log\frac{1}{1-z}\right)^{-1}\right).$$

We thus get for $n\gt 1$ for the LHS $$- (n-1)! (-1)^n [z^{n-1}] \left(\log\frac{1}{1-z}\right)^{-1}$$ and for the RHS $$- (n-1)! (-1)^n [z^n] z\left(\log\frac{1}{1-z}\right)^{-1}.$$

These two are the same by inspection, QED.

$\endgroup$
4
$\begingroup$

Here is a re-write of my first proof with somewhat better aesthetics.

Suppose we seek to show that $$\sum_{k=1}^n \frac{B_k}{k} (-1)^{n-k} {n-1\brack k-1} = -\frac{1}{n} \sum_{k=1}^n \frac{1}{k+1} (-1)^{n-k} {n\brack k}.$$

Observe that using the EGF of the Stirling numbers of the first kind we have $${n\brack k} = \frac{n!}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z^{n+1}} \frac{1}{k!}\left(\log\frac{1}{1-z}\right)^k \; dz.$$

and using the EGF of the Bernoulli numbers we also have $$B_k = \frac{k!}{2\pi i} \int_{|w|=\epsilon} \frac{1}{w^{k+1}} \frac{w}{\exp(w)-1} \; dw.$$

The first of these controls the range and we may extend the sum to infinity, obtaining for the LHS $$ \frac{(n-1)! \times (-1)^n}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z^n} \int_{|w|=\epsilon} \frac{1}{\exp(w)-1} \sum_{k\ge 1} (-1)^k \frac{1}{w^{k}} \left(\log\frac{1}{1-z}\right)^{k-1} \; dw \; dz.$$

This is $$- \frac{(n-1)! \times (-1)^n}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z^n} \int_{|w|=\epsilon} \frac{1}{\exp(w)-1} \frac{1}{w} \left(1+\frac{1}{w} \log\frac{1}{1-z}\right)^{-1} \; dw \; dz \\ = - \frac{(n-1)! \times (-1)^n}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z^n} \int_{|w|=\epsilon} \frac{1}{\exp(w)-1} \left(w+\log\frac{1}{1-z}\right)^{-1} \; dw \; dz.$$

Extracting the residue from the pole at $w=0$ we obtain $$- \frac{(n-1)! \times (-1)^n}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z^n} \left(\log\frac{1}{1-z}\right)^{-1} \; dz.$$

Next do the RHS, getting $$-\frac{1}{n} (-1)^n\frac{n!}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z^{n+1}} \sum_{k\ge 1} (-1)^k \frac{1}{(k+1)!}\left(\log\frac{1}{1-z}\right)^k \; dz.$$

The inner term is $$-\left(\log\frac{1}{1-z}\right)^{-1} \sum_{k\ge 1} (-1)^{k+1} \frac{1}{(k+1)!}\left(\log\frac{1}{1-z}\right)^{k+1} \\ = -\left(\log\frac{1}{1-z}\right)^{-1} \left(-1+ \log\frac{1}{1-z} + \exp\left(-\log\frac{1}{1-z}\right)\right) \\ = -\left(\log\frac{1}{1-z}\right)^{-1} \left(-1+ \log\frac{1}{1-z} + 1-z\right) = -1 + z\left(\log\frac{1}{1-z}\right)^{-1}.$$

This gives for the RHS integral $$ -\frac{1}{n} \frac{n!\times (-1)^n}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z^{n+1}} \left(-1 + z\left(\log\frac{1}{1-z}\right)^{-1}\right) \; dz.$$

When $n\ge 1$ this simplifies to $$-\frac{(n-1)!\times (-1)^n}{2\pi i} \int_{|z|=\epsilon} \frac{1}{z^{n+1}} z\left(\log\frac{1}{1-z}\right)^{-1} \; dz$$ which is the same as the LHS, QED.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.